2020
DOI: 10.1038/s41598-020-70606-w
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of intra-ocular pressure in glaucoma with and without dry eye

Abstract: the management of intra-ocular pressure (iop) is important for glaucoma treatment. iop is recognized for showing seasonal fluctuation. Glaucoma patients can be at high risk of dry eye disease (DeD). We thus evaluated seasonal variation of iop with and without DeD in glaucoma patients. this study enrolled 4,708 patients, with mean age of 55.2 years, who visited our clinics in Japan from Mar 2015 to Feb 2017. We compared the seasonal variation in IOP (mean ± SD) across spring (March-May), summer (June-August), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Our findings are supported by other studies in healthy subjects 4 , 17 , 18 : One study with 103 healthy Chinese participants found an IOP difference of 1.4 ± 0.7 mm Hg between winter and summer, with higher IOP in winter months. 3 Analyses in this subject area in Chicago, Illinois, United States, recorded an IOP peak in December/January (15.7 ± 3.7/15.7 ± 3.8 mm Hg) and lowest IOP in September (14.5 ± 3.1 mm Hg).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are supported by other studies in healthy subjects 4 , 17 , 18 : One study with 103 healthy Chinese participants found an IOP difference of 1.4 ± 0.7 mm Hg between winter and summer, with higher IOP in winter months. 3 Analyses in this subject area in Chicago, Illinois, United States, recorded an IOP peak in December/January (15.7 ± 3.7/15.7 ± 3.8 mm Hg) and lowest IOP in September (14.5 ± 3.1 mm Hg).…”
Section: Discussionsupporting
confidence: 91%
“… 17 Similarly, studies examining glaucoma patients concluded that IOP is subject to periodic IOP changes. 4 , 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…However, there was no correlation between IOP and tear film osmolarity or TFBUT in these patients. Similarly, in a study of 4708 normal subjects and glaucoma patients, there were no differences in IOP between patients with and without dry eye disease in either group 28 …”
Section: Discussionmentioning
confidence: 85%
“…Exploring the signs that influence DED symptoms can help establish the necessity for additional DED metrics. 5…”
mentioning
confidence: 99%
“…Exploring the signs that influence DED symptoms can help establish the necessity for additional DED metrics. 5 In the suggested diagnostic criterion, both sign and symptom measurements are important tools for monitoring DED progression and response to treatment. 2 As the most commonly used measurement, subjective symptoms can be evaluated using the Ocular Surface Disease Index (OSDI) or other questionnaires, and tear break-up time (TBUT) is used to evaluate tear film stability, which is considered as the key sign of DED.…”
mentioning
confidence: 99%